2019
DOI: 10.1155/2019/2408946
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of the Association between Polymorphisms in XRCC1, ERCC2, and XRCC3 and Prognosis in Hepatocellular Carcinoma: A Meta-Analysis

Abstract: Purpose. Associations between XRCC1, XRCC3, and ERCC2 gene polymorphism and prognosis have been investigated in several cancers. The aim of this meta-analysis was to assess the prognostic value of XRCC1, XRCC3, and ERCC2 gene polymorphism in hepatocellular carcinoma (HCC). Methods. A systematic literature search was performed to identify relevant studies in PubMed, Embase, and the Cochrane library up to December 2018. The prognostic values of XRCC1, XRCC3, and ERCC2 polymorphisms in HCC were estimated using cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Enriched genes such as NUSAP1 [Garrido-Rodríguez et al 2019], ASF1B [Han et al 2018] and PRKAA2 [Zhang et al 2020] were associated with proliferation of various cancer types cells, but these genes may be linked with proliferation of hepatoblastoma cells. SNP in enriched genes such as ERCC2 [Zhao et al 2019] and MSH2 [Zhu et al 2018] were involved in progression of hepatocellular carcinoma, but these polymorphic genes may be linked with development of hepatoblastoma. Enriched genes such as TTK (TTK protein kinase) [Miao et al 2016], MKI67 [Yang et al 2017], TET1 [Lin et al 2015], DLGAP5 [Liao et al 2013] and SMYD2 [Zuo et al 2018] were involved in proliferation of hepatocellular carcinoma cells, but these genes may be responsible for proliferation of hepatoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enriched genes such as NUSAP1 [Garrido-Rodríguez et al 2019], ASF1B [Han et al 2018] and PRKAA2 [Zhang et al 2020] were associated with proliferation of various cancer types cells, but these genes may be linked with proliferation of hepatoblastoma cells. SNP in enriched genes such as ERCC2 [Zhao et al 2019] and MSH2 [Zhu et al 2018] were involved in progression of hepatocellular carcinoma, but these polymorphic genes may be linked with development of hepatoblastoma. Enriched genes such as TTK (TTK protein kinase) [Miao et al 2016], MKI67 [Yang et al 2017], TET1 [Lin et al 2015], DLGAP5 [Liao et al 2013] and SMYD2 [Zuo et al 2018] were involved in proliferation of hepatocellular carcinoma cells, but these genes may be responsible for proliferation of hepatoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 | 6287 served two meta-analysis reports that studied the correlation of the XRCC1 (rs25487*p.Gln399Arg) variant with the susceptibility of HCC but with unconvincing conclusions. 24,46 A recent meta-analysis study done among 24 case-control reports revealed that the XRCC1 (rs25487* 399Gln) allele was significantly increased with the progression of HCC under different genetic models (p < 0.05). 24 Absolutely not, another meta-analysis report indicated no significant association of the XRCC1 (rs25487*p.Gln399Arg) variant with the development of HCC under allelic and dominant models.…”
Section: Discussionmentioning
confidence: 99%
“…24 Absolutely not, another meta-analysis report indicated no significant association of the XRCC1 (rs25487*p.Gln399Arg) variant with the development of HCC under allelic and dominant models. 46 Besides that, our team recognized two reports that examined the correlation of the XRCC1 (rs25487*p.Gln399Arg) variant with the increased risk of HCC among Egyptian subjects but in the provinces rather than the delta region of Egypt. 13,47 In a study performed among 50 HCC patients from the South Valley of Egypt, the authors revealed that the XRCC1 (rs25487*399Gln) allele was significantly increased with the progression of HCC (p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA helicase encoded by the excision repair cross-complementing group 2 gene (ERCC2), also called xeroderma pigmentosum group D (XPD), is involved in basal cellular transcription and NER of DNA lesions [51]. To date, a number of studies have implicated the role of genetic polymorphism within ERCC2 gene in various cancers, such as gastric, pancreatic, glioma, bladder, and hepatocellular carcinoma [52][53][54][55][56][57]. The most studied polymorphisms rs13181 (Lys751Gln) and rs238406 (Arg156Arg) were demonstrated to alter the function of encoded protein, and, in consequence, influence on DNA repair capacity [58,59].…”
Section: Discussionmentioning
confidence: 99%